2015
DOI: 10.1037/emo0000023
|View full text |Cite
|
Sign up to set email alerts
|

Why is happy–sad more difficult? Focal emotional information impairs inhibitory control in children and adults.

Abstract: This study compared the relative difficulty of the happy-sad inhibitory control task (say "happy" for the sad face and "sad" for the happy face) against other card tasks that varied by the presence and type (focal vs. peripheral; negative vs. positive) of emotional information in a sample of 4- to 11-year-olds and adults (N = 264). Participants also completed parallel "name games" (direct labeling). All age groups made more errors and took longer to respond to happy-sad compared to other versions, and the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 100 publications
1
39
2
Order By: Relevance
“…Second, the role of inhibitory control in the initial emergence of lie-telling in young children was further supported by the current results. Researchers have found evidence that children perform differently on measures of inhibitory control depending on the nature of the task (e.g., inhibiting emotions vs. types of words; Kramer, Lagattuta, & Sayfan, 2015). It is also among the first to show that mental state understanding may be more predictive of early lie-telling behaviour than inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the role of inhibitory control in the initial emergence of lie-telling in young children was further supported by the current results. Researchers have found evidence that children perform differently on measures of inhibitory control depending on the nature of the task (e.g., inhibiting emotions vs. types of words; Kramer, Lagattuta, & Sayfan, 2015). It is also among the first to show that mental state understanding may be more predictive of early lie-telling behaviour than inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were separated into these groups based on prior research showing developmental gains in control of attention (Anderson, 2002) and EF (Kramer et al, 2015; Lagattuta et al, 2011) between these ages. Child participants were recruited through a pool of past participants, research fliers, and participant referral from areas surrounding a university town.…”
Section: Methodsmentioning
confidence: 99%
“…There are substantial gains in working memory (WM; the capacity to keep multiple pieces of information in mind) and inhibitory control (IC; the ability to regulate dominant responses) between the ages of 3 and 10 and between childhood and adulthood (Best & Miller, 2010; Conklin, Luciana, Hooper, & Yarger, 2007; Kramer, Lagattuta, & Sayfan, 2015; Lagattuta, Sayfan, & Monsour, 2011; Zelazo, Carlson, & Kesek, 2008). Higher WM and IC may enable participants to direct their attention more toward positive, pleasant images.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While work with young children often uses just error rates (e.g., Montgomery & Koeltzow, 2010; Sabbagh, Xu, Carlson, Moses, & Lee, 2006) , research with older children and adults frequently relies on response times (e.g., Prencipe et al, 2011). Moreover, prior work has demonstrated that error rates and cumulative response time are strongly correlated (Kramer, Lagattuta, & Sayfan, 2015; Lagattuta et al, 2011), and both have been associated with advanced ToM (Kennedy et al, 2015; Lagattuta et al, 2010, 2014). …”
Section: Methodsmentioning
confidence: 99%